Women who were sexually abused as children : mothering, resilience, and protecting the next generation - Gil, Teresa, 1958- (Rowman & Littlefield, 2018)
This book highlights the resilient capacities of mothers who have experienced childhood sexual abuse and gives them the opportunity to break their silence, share their struggles, and give voice to their experiences, pains, and triumphs. By offering their stories, Teresa Gil sheds light on the challenges of mothering after childhood sexual abuse.